Evaluating intellectual development of horticultural students: the impact of two teaching approaches using Perry’s scheme of intellectual development as measured by the learning environment preference - Lavis, Catherine Camille (Kansas State University, 2005)
This phenomenological study explored horticultural students’ intellectual development as defined by William Perry’s Scheme. Perry’s theory of intellectual development helps describe the progression in college student thinking from simple to complex. These patterns of development act as filters through which a student ascribes meaning to their world. The objectives of this study were to: 1) explore the reliability of using the Learning Environment Preference Inventory (LEP) instrument’s Cognitive Complexity Indicator (CCI) scores as a tool to recognize the positions of cognitive complexity of horticultural students, the nature of this complexity and if gender, age, class status, or previous horticultural experience would influence CCI scores; 2) determine if specific teaching methods designed to promote active involvement at a higher level of exchange than lecture might influence scores; 3) describe the effects of the collaborative interactions with classmates and instructor; 4) determine whether student journals would reveal changes in their cognitive complexity or perception of learning as a result of their learning environment and; 5) discover other significant issues that could produce advancement along the Perry scale. Students in this study began their experiences no lower than Perry position two and ranged as high as position four. The initial CCI scores affirmed that many upper-division horticultural students were still operating in Perry positions two and three. Analysis of the interviews revealed: 1) that instructor techniques may positively or negatively influence individual students ideal learning environment; 2) there are significant issues that influence student ideal learning environments; 3) learning is viewed as the responsibility of the instructor, and; 4) students prefer hands-on learning. The students CCI scores did not show upward movement as a direct result of collaborative learning, although the voices of several students expressed both benefits and drawbacks of this type of learning. Journal writing did not reveal any changes in students’ level of thinking or perception of learning but they did reveal other aspects of student learning and attitudes. An understanding of Perry’s Scheme helped the researcher to recognize that student perspective, behavior, and performance is conditioned more by the students’ cognitive complexity than by peer interaction or by teaching methodology.
Keywords: Horticultural students; Intellectual development using William Perry's Scheme; Learning environment preference; Horticultural students and cognitive complexity; Intellectual development and collaborative learning; Agriculture, Agronomy (0285); Education, Agricultural (0517); Education, Higher (0745)